New genus of Pleminiini Brunner von Wattenwyl, 1878 (Orthoptera: Tettigoniidae: Pseudophyllinae) from the Colombian Andes - Mendes, Diego M. M.; Pádua, Diego G.; Araujo, Rodrigo O.; Mazariegos, Luis A.; Fernandes, Daniell R. R. (Zootaxa, 2024)
The Pleminiini tribe (Pseudophyllinae: Tettigoniidae) currently comprises 51 genera and 227 valid species with a Neotropical and Afrotropical distribution. Herein, the new monotypic genus Muscuspina Mendes gen. nov. is described with a new species, Muscuspina neblina Mendes sp. nov., distributed in the Andean montane forest of Antioquia, Colombia. Maps and natural history observations are provided.